A Content Analysis of Research on Disability: American Counseling Association Journals Between 2003 and 2013. Issue 4 (October 2016) - Woo, Hongryun; Goo, Minkowan; Lee, Myungkyung
Abstract : This content analysis provides an overview of disability articles published in 10 major American Counseling Association journals between 2003 and 2013. In addition to the number of disability articles published during this time period, other content areas such as authorship and institutional contributors; methodology, location, and application settings; target populations and sample characteristics; type of disabilities; and topics of interest are identified. Recommendations for counseling scholars to increase the scope of research on disability are provided. Este análisis de contenido proporciona una visión general de los artículos sobre discapacidad publicados en 10 revistas principales de la Asociación Americana de Consejería (American Counseling Association) entre 2003 y 2013. Además del número de artículos sobre discapacidad publicados durante este periodo, se identifican otras áreas de contenidos, como la autoría y contribuidores institucionales, la metodología, ubicación y lugares de aplicación, las poblaciones observadas y características de los grupos de muestra, los tipos de discapacidad, y los temas de interés. Se proporcionan recomendaciones para que los expertos académicos en consejería puedan ampliar el alcance de las investigaciones sobre discapacidad.